KEGIATAN KETERAMPILAN MELIPAT KERTAS (ORIGAMI) PADA LANSIA DI RUMAH BAHAGIA BINTAN - Suangga, Fitriany; Handayani, Wulan; Agustina, Puti; Lisandari , Yani; Kurniawan, Riski (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2024)
There are various simple methods that can be adopted to improve both the motor and cognitive skills of an individual. One option is to engage in activities that require both physical engagement and thinking. Some of the activities that can be undertaken include coloring, playing puzzles, and making different types of crafts. For example, NERS Professional Students have adopted the activity therapy of making crafts from origami as an effective way to practice fine motor skills. The process of folding, cutting, and pasting colorful paper not only encourages finger movements, but also helps improve hand-eye coordination. Moreover, this activity is not only a form of motor development, but also promotes aspects of creativity through making unique shapes out of the paper. Furthermore, playing origami also brings cognitive benefits by involving accuracy, focus, and the ability to understand instructions. Seniors participating in this activity are required to listen carefully to instructions and apply them, thus helping to train memory and comprehension. Overall, the goal of origami activity therapy is not only to improve motor skills and creativity, but also to reduce the impact of hospitalization on the elderly and delay any cognitive decline that may occur.